Effect of combination of tofu dregs and banana waste as a growth media on nutrient content and density of Black Soldier Fly larvae (Hermetia illucens) - Ubaidillah, Muhammad Zaki; Sjofjan, Osfar (Jurnal Ilmu Peternakan Terapan, 2024)
The aim of this research was to determine the effect of the combination of tofu dregs and banana waste as a growing medium on the nutritional content and density of Black Soldier Fly (Hermetia illucens) larvae. This research uses laboratory experiments with five treatments and four replications. The growing medium used is a combination of tofu dregs and banana waste. Treatments consisted of T0 (100% tofu dregs), T1 (100% banana waste), T2 (25% tofu dregs + 75% banana waste), T3 (50% tofu dregs + 50% banana waste), and T4 (tofu dregs 75% + banana waste 25%). Parameter measured was the dry matter content, crude protein, crude fat, crude fiber, and density of Black Soldier Fly larvae. Data were analyzed using a Completely Randomized Design and if there was a real effect between treatments, it was continued with the Duncan Multiple Range Test (DMRT). The research results of the combination of tofu dregs growing media and banana waste had a significant (P<0.05) effect on crude fiber content and a very significant (P<0.01) effect on crude protein and crude fat content. Using a combination of tofu dregs and banana waste had no significant effect (P>0.05) on the dry matter content and density of Black Soldier Fly larvae. The conclusion of the research was the best result in T4 with a dry matter content of 27.13%, crude protein 11.81%, crude fat 8.43%, crude fiber 5.18%, and density 162.79 g/L. of black soldier fly larvae.